MicroWorld: Development of Microorganisms Learning Application for Year 6 Using Augmented Reality Technology - Liew, Chui Yi; Othman, Muhammad Fakri (Applied Information Technology And Computer Science, 2023)
Microorganisms are tiny living things to be seen with the naked eye and a microscope is required. They are indispensable and bring benefits to our daily life. However, only a small piece of knowledge about microorganisms is offered in the science year 6 Dual Language Programme (DLP) textbook which causes the students might misunderstanding towards microorganisms are all harmful to us. Besides, the images provided in the textbook are static which leads to difficulty in learning. Therefore, an application called MicroWorld is designed and is expected to act as a learning aid for the target users who are twelve-year-old primary school Year 6 students. Multimedia Mobile Content Development (MMCD) methodology is utilized to develop this learning application on the Android platform. Positive feedback is obtained in the beta testing with an average score of 94.58% which falls in the acceptable range of the scale of the SUS score.